Psychological, physiological, and biochemical correlations after negative emotional videos in college students with and without premenstrual syndrome - Xing, Jingyu; Wu, Hao; Wang, Xue; Yi, Shuang; Wei, Yu; Zhao, Yan; Hu, Xingang (Frontiers in Psychiatry, 2023)
Women with premenstrual syndrome (PMS) suffer heavily from emotional problems, the pathogenesis of which is believed to be related to the hypothalamic-pituitaryadrenal (HPA) axis, autonomic nervous system (ANS) and central nervous system (CNS). We took into account all 3 aspects to observed the psychological, physiological and biochemical correlations under anger and sadness in college students with and without PMS. 33 students with PMS and 24 healthy students participated in the emotion induction experiment, and were required to fill out self-report scales. Their salivary cortisol (SCort), skin conductivity level (SCL), heart rate variability (HRV), blood pressure (BP) and electroencephalogram (EEG) data were collected at the resting stage and 10-15 minutes after each video. Compared to healthy controls, students with PMS showed lower SCort level and higher VLF at rest and similar response patterns in ANS and HPA axis after emotional videos, but different activities in CNS in all conditions.The decreases in SBP during angry video, SCort after angry and neutral videos, and increases in θ band power during sad video were moderately correlated with increases in PMS score. No intergroup differences were found in self-report emotions.